PWE-072 The Effects Of Anti-tnf Therapy On Growth In Ibd In Scottish Children. (9th June 2014) - Cameron, FL; Al-Towati, M; Bisset, WM; Ahmed, SF; Wilson, DC; Russell, RK
Abstract : Introduction: Growth failure is well-recognised in paediatric IBD (PIBD; <18 years). Evidence (usually case series from single/multiple centres) shows anti-TNF therapies improve linear growth. We aimed to examine if anti-TNF therapy improves growth in a PIBD population-based cohort. Methods: Retrospective review of all children receiving anti-TNF (infliximab (IFX) and adalimumab (ADA)) from 2000–2012 in paediatric services in Scotland. Height (Ht), weight and Tanner stage were collected at 3 times: 12 months before anti-TNF (T-12), start of anti-TNF (T0) and 12 (T+12) months after anti-TNF. Ht and growth were converted into standard deviation scores (SDS) and height velocity (HV, cm/ year) were calculated. Results: 97/201 PIBD cases (3ADA, 94 IFX) had 12 month growth data, 58 (59%) males and 90 (93%) Crohn's disease (CD); 84 (87%) received immunomodulators and 47 (48%) corticosteroids at T0. Median age at diagnosis was 10.3 years. In IFX treated, mean Ht SDS T-12 was -0.67 +/-1.1; improvement was then seen from T0 -0.82 +/-1.1 to T+12 -0.74 +/-1.1 (p = 0.031). Mean ΔHtSDS improved from -0.16 +/-0.38 at T0 to 0.08 +/- 0.36 at T+12 (p < 0.001) with HV improving from 3.9 cm/yr +/-2.5 at T0 to 5.0 cm/yr +/-2.9 (p = 0.003). 56 (60%) entered remission, HtSDS improved from -0.77 +/- 1.1 at T0 to -0.56 (+/-1.1) at T+12 (p = 0.0004). ΔHtSDS improved from T0 -0.14 (+/-0.04) to 0.21 (+/-0.04) at T+12 (p < 0.001) and HV from 4.0 cm/yr (+/-2.3) at T0 to 5.6cm/yr (+/-2.9) at T12 (p = 0.003). 44/94 IFX (48%) were Tanner stage 1–3; 40 CD. Mean HtSDS decreased from -1.0 (+/- 1.1) at T-12 to -1.2 (+/-1.3) at T+12 but, HV 3.6 cm/yr (+/-2.1) at T0 improved to 5.5cm/yr (+/-2.7) at T12 (p < 0.001). In Tanner 4and5, no change in HtSDS or ΔHtSDS was seen. 61 (65%) had disease for ≥2 years at start of IFX, HtSDS improved from -0.77+/-1.2 at T0 to -0.65+/-1.2 at T+12 (p = 0.007) whilst disease <2 years (n = 33) had no change; HtSDS -0.93+/- 0.97 at T0 and -0.92+/-0.89 at T+12 (p = 0.89). Improvement was seen in height velocity in ≥ 2; years HV 4.1+/-2.5 at T0 and 5.0+/-2.9 at T+12 (p = 0.039) compared to HV <2 years 3.6+/-2.3 at T0 and 4.8+/-3.0 at T+12 (p = 0.08). Greater improvement in ΔHtSDS in ≥2 yrs; ΔHtSDS at T0 -0.12+/-0.35 improved to 0.12+/-0.33 at T+12 (p < 0.001) vs. -0.22+/-0.43 at T0 to 0.16+/-0.4 (p = 0.018) for <2 yrs. In UC (n = 7) no change was seen in ΔHtSDS or HV at T-12, T0 or T+12 (p 0 >0.05). Conclusion: Improvements in HtSDS and height velocity at 12 months were seen in the whole cohort. In Tanner 1–3 improvement was only seen in HV after 12 months with no improvement in Ht sSDS. No improvement in height noted in UC. Further follow up will determine if growth improvement is maintained or further improves. Disclosure of Interest: None Declared.